Soil Quality Index of Tropical Peatlands Affected by Canal Blockages - Nusantara, Rossie Wiedya; Gusmayanti, Evi Gusmayanti; Sudrajat, Jajat Sudrajat (Faculty of Geography, Universitas Gadjah Mada, 2025)
This study aimed to determine the Soil Quality Index (SQI) of peatlands where canal blocking was implemented. The research was conducted in two villages in Kubu Raya District, West Kalimantan Province e.g. Madu Sari and Teluk Empening. The sites in Madu Sari were impacted by permanent canal blocking with horticultural crops (M1) and corn (M2), while the sites in Teluk Empening had simple canal blocking with rubber (E1) and horticultural crops (E2). A total of 24 peat soil samples were collected from a depth of 0-20 cm. These samples were analyzed for nineteen physical, chemical, and biological indicators, including peat depth, water-table depth, bulk density, water content, total porosity, permeability, pH, organic carbon, total nitrogen, CN ratio, available phosphorus, exchangeable sodium, exchangeable potassium, exchangeable calcium, exchangeable magnesium, cation exchange capacity, base saturation, ash content, and earthworm. Statistical tests used ANOVA and brown-forsythe to determine the effect of location, as well as tukey test and howell games for further tests. The reduction from 19 to 13 indicators was based on the correlation of the constituent indicators with a value of r>0.5. There are 3 steps to determine SQI, namely to identification of the minimum data set (MDS), (2) the scoring of the MDS indicators, and (3) the calculation of the SQI value. The SQI values for the sites were 0.64 (good) for M1, 0.56 (moderate) for M2, 0.50 (moderate) for E1, and 0.52 (moderate) for E2, reflecting varying levels of soil quality across the locations. The addition of organic matter from manure has a positive impact on soil quality compared to the application of inorganic fertilisers and intensive tillage.Received: 2024-08-19 Revised: 2024-11-15 Accepted: 2025-08-15 Published: 2025-08-19